(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Globally, the worlds Portland cement production contributes about 1.6 billion tons of CO2 or about 7% of global loading of CO2 into the atmosphere. The manufacture of Portland cement releases Carbon dioxide that is significant contributor of Green house gas emissions to the atmosphere. Geopolymer is more eco friendly material and a strong alternative to Portland cement. Geopolymer mortar can be used in Ferro cement instead of other conventional materials like cement mortar. Ferro cement is a composite material formed by closely spaced wire mesh which uses wire meshes as reinforcement. Ferrocement has high tensile strength, minimum thickness, ease of mould ability. Experimental investigation has been carried out to study the Effect of Geopolymer mortar in Ferrocement for variation in mesh size and number of layers. For this, tensile testing was done on Geo-ferrocement specimens of size 750 x 60 x 30 mm reinforced with single, double, triple layer using variation in meshes of different sizes. Similarly, compression testing of cubical specimens of size 70 x 70 x 70 mm reinforced with single, double, triple layer of meshes of different sizes was done. Test results show that tensile and compressive strength of specimen’s increases with increase in number of layer of meshes and mesh size also played an important role in strengthening of specimens. Compressive strength of single mesh layer in Geopolymer mortar is greater than single mesh layer in conventional cement mortar by approximately 5 %. For double layer mesh, specimens with Geopolymer mortar show greater strength than specimens with conventional cement mortar by 5-6 %.